Ukrainian charm exorcist dialogues: the structure, semantics, function (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article is devoted to the semantic, structural and functional peculiarities of one group of Ukrainian some-phrase charm exorcist texts – texts-dialogues. These peculiarities are provoked by task and magic function of these texts. Charm exorcist dialogues reflect the world outlook and psychological peculiarities of speakers, specifically verbal display of  magic principle analogy.
Keywords: charm exorcist text; dialog; magic function